Antioxidant and antibacterial screening of honey of Hiterotrogona itama collected from differents meliponiculture areas in East Kalimantan, Indonesia - SUROTO HADI SAPUTRA; BERNATAL SARAGIH; IRAWAN WIJAYA KUSUMA; ENOS TANGKE ARUNG (Nusantara Bioscience, 2021)
Abstract. Saputra SH, Saragih B, Kusuma IW, Arung ET. 2021. Antioxidant and antibacterial screening of honey of Hiterotrogona itama collected from different meliponiculture areas in East Kalimantan, Indonesia. Nusantara Bioscience 13: 232-237. Heterotrigona itama (Cockerell, 1918) is a stingless bee in several areas in East Kalimantan of Indonesia. This study aimed to analyze the phytochemicals and antioxidant activity of honey of this stingless bee from several regions in East Kalimantan. Phytochemical testing was carried out qualitatively, while antioxidant activity was performed using DPPH (1.1-diphenyl-2-picrylhydrazyl-radical) radical scavenging assay. Furthermore, the antimicrobial activity of Staphylococcus aureus and Escherichia coli was performed through in vitro tests. The results showed that the honey of stingless H. itama bee collected from five cultivated areas in East Kalimantan contained flavonoids, coumarin, steroids, and carotenoids, some of which had alkaloids and tannin compounds. The antioxidant activity (IC50) was observed between 43,54 ppm-71,27 ppm, while the strong antimicrobial activity of this honey was found against S. aureus and E. coli.